The Implementation of Buddhist Religious Education Character-Based on Strengthening Religious Moderation Students at School - Dharma Yana Saputra; Komang Sutawan; Burmansah Burmansah; Sidartha Adi Gautama; Susanto Susanto (Universitas Sebelas Maret, 2024)
Abstract: This study aims to determine the effect of implementing Buddhism-based character education on the strengthening of religious moderation of Buddhist students in public high schools in one of the districts of North Lombok, West Nusa Tenggara Province. The problems that occur to students are making religious differences a trigger for conflicts and fights at school, making religion a joke, which has the potential to offend their friends, and lacking understanding and appreciation for religious diversity so that they are quickly involved in intolerant behavior, being influenced by a hostile environment, thus strengthening intolerant attitudes towards religious differences, feeling that their religion is superior, therefore underestimating other faiths. This study uses a quantitative approach with a survey method. The population in the study is 10th, 11th, and 12th-grade students with a total of 128 people; the sample in this study is 97 people, and the Proportional Random Sampling technique obtained the sample. The results showed a positive and significant influence between Buddhist religious education character-based and religious moderation, with a count of 14.547 and a significance value (p) of 0.000 < 0.05. From the results of simple regression analysis, the R Square value was obtained at 0.690. This means that Buddhist religious education character-based affects religious moderation by 69%, and factors outside this research model influence the remaining 31%. Based on the results, the school should be able to develop religious education with character to strengthen religious moderation in the daily lives of students, the school environment, and the community.